A Systematic Review of DNA Methylation and Gene Expression Studies in Posttraumatic Stress Disorder, Posttraumatic Growth, and Resilience. Issue 2 (17th January 2020) - Mehta, Divya; Miller, Olivia; Bruenig, Dagmar; David, Georgina; Shakespeare‐Finch, Jane
Abstract: Most people will experience a traumatic event within their lifetime. One commonly recognized response to trauma exposure is posttraumatic stress disorder (PTSD). The biological underpinnings of PTSD, including epigenetic mechanisms of DNA methylation and gene expression, have been studied intensively. However, psychological posttrauma responses vary widely and can include positive outcomes, such as posttraumatic growth (PTG) and, more commonly, resilience. The aim of this systematic review was to summarize the current DNA methylation and gene expression data with respect to three potential posttrauma responses: PTSD, PTG, and resilience. A literature search identified 486 studies, 51 of which were deemed eligible for inclusion (total N = 10, 633). All included studies examined PTSD and consistently implicated DNA methylation and gene expression changes in hypothalamic–pituitary–adrenal axis and inflammatory genes. Ten studies acknowledged resilience as a posttrauma response, but only two studies examined epigenetics and gene expression using a scale to measure resilience. Low resilience was associated with gene expression patterns in immune and dopamine genes, and high resilience was associated with a blunted inflammatory response. No studies examined epigenetic or gene expression changes associated with PTG. These findings highlight a focus on pathogenic research, which has failed to adequately acknowledge and measure positive posttrauma outcomes of PTG and resilience. Future research should examine DNA methylation and gene expression changes associated with PTG and resilience in addition to PTSD in order to gain a more comprehensive picture of an individual's well‐being following exposure to trauma. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Una revisión sistemática de la metilación del ADN y los estudios de expresión génica en el trastorno de estrés postraumático, crecimiento postraumático y resiliencia REVISIÓN DE LOS RESULTADOS DE EPIGENÉTICA Y TRAUMA La mayoría de las personas experimentarán un evento traumático durante su vida. Una respuesta comúnmente reconocida al trauma es el trastorno de estrés postraumático (TEPT). Los fundamentos biológicos del TEPT, incluidos los mecanismos epigenéticos de la metilación del ADN y la expresión génica, se han estudiado intensamente. Sin embargo, las respuestas psicológicas al trauma varían ampliamente y pueden incluir resultados positivos, como el crecimiento postraumático (CPT) y, más comúnmente, la resiliencia. El objetivo de esta revisión sistemática fue resumir los datos actuales de metilación del ADN y expresión génica con respecto a tres posibles respuestas postraumáticas: TEPT, CPT y resiliencia. Una búsqueda bibliográfica identificó 486 estudios, 51 de los cuales se consideraron elegibles para su inclusión ( N total = 10, 633). Todos los estudios incluidos examinaron el TEPT y los cambios en la metilación del ADN y la expresión génica implicados sistemáticamente en el eje hipotalámico‐pituitario‐adrenal y en los genes inflamatorios. Diez estudios reconocieron la resiliencia como una respuesta postraumática, pero solo dos estudios examinaron la epigenética y la expresión genética utilizando una escala para medir la resiliencia. La baja resiliencia se asoció con patrones de expresión génica en los genes inmunitarios y de dopamina, y la alta resiliencia se asoció con una respuesta inflamatoria embotada. Ningún estudio examinó los cambios epigenéticos o de expresión génica asociados con el CPT. Estos hallazgos destacan un enfoque en la investigación patógena, que no ha logrado reconocer ni medir adecuadamente los resultados postraumáticos positivos del CTG y la resiliencia. Las investigaciones futuras deben examinar la metilación del ADN y los cambios en la expresión génica asociados con el CPT y la resiliencia además del TEPT para obtener una imagen más completa de bienestar del individuo después de la exposición a un trauma. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐18‐0461.R2 Mehta A systematic review of DNA methylation and gene expression studies in Posttraumatic Stress Disorder, posttraumatic growth and resilience Traditional Chinese 標題: 有關創傷後壓力症、創傷後成長與恢復力的DNA甲基化和基因表現研究的系統性評估 撮要: 大多數人一生中都會經歷到創傷事件。創傷後壓力症(PTSD)是普遍的創傷反應。過往有大量研究檢視PTSD的生物結構, 包括DNA甲基化和基因表現的表觀遺傳學機制。不過, 各人面對創傷的心理反應不盡相同, 而且亦可能包含正向的結果, 例如創傷後成長(PTG)和恢復力, 而後者較為普遍。本系統性評估旨在概述有關三種潛在創傷後反應 (PTSD、PTG、恢復力) 當前的DNA甲基化和基因表現數據。我們搜尋文獻, 找出486個研究, 當中51個符合我們的檢視範圍 (總 N = 10, 633), 它們全都檢視PTSD, 並一致地包含下視丘‐垂體‐腎上腺軸 (HPA軸) 及炎症基因的DNA甲基化和基因表現改變數據。共有10個研究承認恢復力為一種創傷後反應, 但只有2個研究以量表測量恢復力以檢視表觀遺傳學和基因表現。恢復力低跟免疫基因及多巴胺基因的基因表現模式有關, 而恢復力高則與遲鈍的炎症反應有關。並無研究檢視與PTG相關的表觀遺傳學或基因表現改變。這些發現凸顯過往研究傾向專注於致病研究, 使我們對PTG和恢復力這些正向的創傷後結果缺乏認識和測量。未來的PTSD研究, 應額外檢視與PTG和恢復力相關的DNA甲基化和基因表現改變, 以更全面地理解個人經歷創傷後的健康轉變。 Simplified Chinese 标题: 有关创伤后压力症、创伤后成长与恢复力的DNA甲基化和基因表现研究的系统性评估 撮要: 大多数人一生中都会经历到创伤事件。创伤后压力症(PTSD)是普遍的创伤反应。过往有大量研究检视PTSD的生物结构, 包括DNA甲基化和基因表现的表观遗传学机制。不过, 各人面对创伤的心理反应不尽相同, 而且亦可能包含正向的结果, 例如创伤后成长(PTG)和恢复力, 而后者较为普遍。本系统性评估旨在概述有关三种潜在创伤后反应 (PTSD、PTG、恢复力) 当前的DNA甲基化和基因表现数据。我们搜寻文献, 找出486个研究, 当中51个符合我们的检视范围 (总 N = 10, 633), 它们全都检视PTSD, 并一致地包含下视丘‐垂体‐肾上腺轴 (HPA轴) 及炎症基因的DNA甲基化和基因表现改变数据。共有10个研究承认恢复力为一种创伤后反应, 但只有2个研究以量表测量恢复力以检视表观遗传学和基因表现。恢复力低跟免疫基因及多巴胺基因的基因表现模式有关, 而恢复力高则与迟钝的炎症反应有关。并无研究检视与PTG相关的表观遗传学或基因表现改变。这些发现凸显过往研究倾向专注于致病研究, 使我们对PTG和恢复力这些正向的创伤后结果缺乏认识和测量。未来的PTSD研究, 应额外检视与PTG和恢复力相关的DNA甲基化和基因表现改变, 以更全面地理解个人经历创伤后的健康转变。